Wild West lawmen and outlaws - Randolph, Ryan P. (New York : PowerKids Press, 2003)
Historical photographs and easy-to-understand text help describe what life was like in the American West, discussing cattle rustlers, bank robbers, women outlaws, the honor and code of the West, U.S. Marshals, Texas Rangers, and Pinerton Detectives, and their roles in giving the region its wild reputation.
Why was the West so wild? -- Honor and the code of the West -- Cattle rustlers and cattle wars -- Bank robbers -- Women outlaws -- Train robbers -- The law of the West -- Local lawmen and the posse -- U.S. marshals, Texas Rangers, and Pinkerton detectives -- The legacy of the Wild West.
Includes index.
5.7
3-6
Keywords: Frontier and pioneer life -- West (U.S.) -- Juvenile literature; West (U.S.) -- History -- 19th century -- Juvenile literature; Violence -- West (U.S.) -- History -- 19th century -- Juvenile literature; Outlaws -- West (U.S.) -- Biography -- Juvenile literature; Peace officers -- West (U.S.) -- Biography -- Juvenile literature; West (U.S.) -- Biography -- Juvenile literature; West (U.S.) -- History -- 19th century; Peace officers; Robbers and outlaws; West (U.S.) -- History; Peace officers -- Biography; Thieves -- Biography